Hottest, coldest, highest, deepest - Jenkins,Steve (New York Scholastic Inc., 1998)
Describes some of the remarkable places on earth, including the hottest, coldest, windiest, snowiest, highest, and deepest.
G8
Keywords: Geography -- Juvenile literature